PENGEMBANGAN DESAIN KEMASAN PRODUK CLEANER SEPATU YANG BERORIENTASI PADA KEPUASAN KONSUMEN DENGAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Ahmat Abdul Muis Azzarkasi; Christian, Andrastea Zefta; M Faiq Hudaya Zulfa; Matias Junianto Wijoyo; Unggul Bayu Wicaksono; Andung Jati Nugroho (CV. ALIM'SPUBLISHING, 2025)
Max Cleaning, as one of the MSMEs engaged in shoe washing services, has gained the trust of the public thanks to the quality of the washing carried out. Not only does it offer Max Cleaning services, it also sells its products, namely cleaners. Max Cleaning needs to develop packaging for its shoe cleaning products because competition is tight and product packaging is increasingly attractive, useful and at low prices, so it is necessary to develop packaging design. The development of shoe packaging cleaning designs that focus on consumer satisfaction using the Quality Function Deployment (QFD) method lies in the need to understand and fulfill customer preferences and needs in depth. The research objective is to provide an improved design for shoe cleaning packaging products that suit customer needs. Data collection techniques used in research to obtain data from respondents using questionnaires. Based on 5 attributes that influence customer satisfaction, it has a high level of satisfaction and is needed by consumers, namely the unique shoe cleaner packaging product design influences the decision to buy